Not All Women Are Mothers: Addressing the Invisibility of Women Under the Control of the Criminal Justice System Who Do Not Have Children - Michalsen, Venezia; Flavin, Jeanne (The Prison Journal, 2014)
Research has consistently shown that most women under the control of the criminal justice system are mothers. The robustness of this finding has been accompanied by a failure to consider the characteristics and needs of women without children. In this study, we examine data on 1,334 formerly incarcerated women. Findings indicate that while mothers and non-mothers share some characteristics, they differ on several others, most notably demographic profile, mental health, and timing of contacts with the criminal justice system. These results suggest a need to recognize the diversity among women offender groups, particularly when developing policies and programs need.
Keywords: dept.soc; peer-reviewed